2004
DOI: 10.1007/s11102-005-5348-y
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Pathology in Carney Complex Patients

Abstract: Carney complex (CNC) is a familial multiple neoplasia syndrome with features overlapping those of McCune-Albright syndrome (MAS) and multiple endocrine neoplasia (MEN) type 1 (MEN 1). Like MAS and MEN 1 patients, patients with CNC develop growth hormone (GH)-producing pituitary tumors. Occasionally, these tumors are also prolactin-producing, but there are no isolated pro-lactinomas or other types of pituitary tumors. In at least some patients with CNC, the pituitary gland is characterized by hyperplastic areas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 49 publications
1
34
0
2
Order By: Relevance
“…11 The great majority of adenomas arise in a sporadic manner, and only a minority of adenomas are part of hereditary or familial syndromes. 14 Familial syndromes in which GH-secreting adenomas arise include the following: 1) MEN-1, linked to somatic mutations of the tumor suppressor gene MEN-1 located at the 11q13 locus; 8 2) CNC, linked to mutations of the tumor suppressor gene PRKAR1A located at 17q22-24; 49 and less commonly 3) McCune-Albright syndrome, linked to activating mutation of the gsp oncogene located at 20q13 55 (see below). Growth hormone-secreting adenomas linked to either MEN-1 or CNC are believed to correspond to about 3% of all GH-secreting tumors.…”
Section: Molecular Genetics Of Gh-secreting Tumorsmentioning
confidence: 99%
“…11 The great majority of adenomas arise in a sporadic manner, and only a minority of adenomas are part of hereditary or familial syndromes. 14 Familial syndromes in which GH-secreting adenomas arise include the following: 1) MEN-1, linked to somatic mutations of the tumor suppressor gene MEN-1 located at the 11q13 locus; 8 2) CNC, linked to mutations of the tumor suppressor gene PRKAR1A located at 17q22-24; 49 and less commonly 3) McCune-Albright syndrome, linked to activating mutation of the gsp oncogene located at 20q13 55 (see below). Growth hormone-secreting adenomas linked to either MEN-1 or CNC are believed to correspond to about 3% of all GH-secreting tumors.…”
Section: Molecular Genetics Of Gh-secreting Tumorsmentioning
confidence: 99%
“…However, little is known about the precise environmental and genetic factors involved in pituitary tumorigenesis. In CNC, GH-producing pituitary adenomas are observed in w10% of patients (Stratakis et al 2001), and prolactinomas have also been reported in CNC kindreds (Stergiopoulos et al 2004). In both of the Prkar1a C/K mouse models described (Veugelers et al 2004, Kirschner et al 2005, pituitary pathology was not observed.…”
Section: Tissue-specific R Subunit Mouse Modelingmentioning
confidence: 99%
“…GH-and/or PRL-producing are the second most frequently found functional pituitary tumors in early childhood; these tumors in children almost always occur in the familial setting or in the context of known genetic defects: GNAS, menin, PRKAR1A, AIP and p27 (CDKN1B) mutations [21,[32][33][34][35][36]; somato-and/or mammotropinomas become significantly more frequent than corticotropinomas in late childhood, adolescence and adulthood [37].…”
Section: Pituitary Adenomasmentioning
confidence: 99%